A REVIEW OF THE MINIATURIZATION OF MICROSTRIP PATCH ANTENNA BASED ON FRACTAL SHAPES - Froumsia, Dokrom; Yao, Shao-Wen; Jean-Francois, Essiben Dikoudou; Alphonse, Houwe; Kolyang; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2022)
Wireless communication has become ubiquitous in almost every sector, both in military and commercial systems. Communicating objects are getting smaller and smaller. Therefore, the antennae which are the fundamental elements of this circuit must meet the requirements of their integrating environment in terms of bandwidth, multiple frequencies, smaller size and affordability. Microstrip patch antenna (MPA), a priori, should have been the preferred candidate, but the narrowness of its bandwidth is a limitation. Therefore, many techniques have been explored including the use of fractal shapes for improving the performance of this type of antenna. Multiform fractal shapes have been used in various works to achieve the results expected in specific cases to effectively meet the requirements of wireless communication. In this paper, we will do an overview by highlighting the various kinds of fractal geometries which have been the most used in recent years by clearly specifying that the options of miniaturization of microstrip antennae by the theories of Sierpinski and Minkowski are ideal methods and therefore, will drive our future work on miniaturized antenna designs.
Keywords: Fractal Geometry; Iteration Factor; Miniaturization; Crinkle-Shaped